2022
DOI: 10.3389/fonc.2022.775238
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Epithelial-to-Mesenchymal Transition in Radioresistance: Crosslinked Mechanisms and Strategies

Abstract: Radiotherapy exerts a crucial role in curing cancer, however, its treatment efficiency is mostly limited due to the presence of radioresistance. Epithelial-to-mesenchymal transition (EMT) is a biological process that endows the cancer cells with invasive and metastatic properties, as well as radioresistance. Many potential mechanisms of EMT-related radioresistance being reported have broaden our cognition, and hint us the importance of an overall understanding of the relationship between EMT and radioresistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 170 publications
(200 reference statements)
2
17
0
Order By: Relevance
“…In recent works, we have demonstrated for the first time that alterations in glycosylation in tumor cells chronically exposed to chemotherapeutic agents, are able to connect both MDR phenotype and EMT process, since in addition to presenting changes in the expression and/or activity of efflux pumps belonging to the ABC superfamily (ABCB1, ABCC1 and ABCG2) [55,56], the chemoresistant human cancer cell lines also showed increased cell motility, as well as altered expression of epithelial-mesenchymal markers, when compared with their normal counterparts [34,35]. These findings confirm the idea that both accretion of MDR phenotype and the activation of EMT process, which have been considered indispensable for invasion and metastasis [57][58][59], are deeply linked with unusual glycan structures expressed by transformed cells. In our previous study we also observed that the chronic exposure to non-lethal concentrations of cisplatin induced the expression of an isoform of fibronectin (FN), so called oncofetal FN (onf-FN) [35], which may be found in transformed cells, and embryonic samples, but is absent in normal tissues [6].…”
supporting
confidence: 76%
“…In recent works, we have demonstrated for the first time that alterations in glycosylation in tumor cells chronically exposed to chemotherapeutic agents, are able to connect both MDR phenotype and EMT process, since in addition to presenting changes in the expression and/or activity of efflux pumps belonging to the ABC superfamily (ABCB1, ABCC1 and ABCG2) [55,56], the chemoresistant human cancer cell lines also showed increased cell motility, as well as altered expression of epithelial-mesenchymal markers, when compared with their normal counterparts [34,35]. These findings confirm the idea that both accretion of MDR phenotype and the activation of EMT process, which have been considered indispensable for invasion and metastasis [57][58][59], are deeply linked with unusual glycan structures expressed by transformed cells. In our previous study we also observed that the chronic exposure to non-lethal concentrations of cisplatin induced the expression of an isoform of fibronectin (FN), so called oncofetal FN (onf-FN) [35], which may be found in transformed cells, and embryonic samples, but is absent in normal tissues [6].…”
supporting
confidence: 76%
“…We also reveal that the presence of these invasive cells impairs the successful removal of BCBM lesions. Importantly, even if surgery is followed by chemotherapy or radiotherapy, these invasive cells may not be efficiently depleted, since EMT endow cells with properties that can render them resistant to those therapies [21,[58][59][60]. Therefore, targeting EMT can improve surgical resection and may sensitize cells that are left behind to subsequent therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these pathways include TGF-β, Wnt/β-catenin, NOTCH, EGFR, NF-κB, IL-6/STAT3, PI3K-AKT, and ERK. Likewise, specific miRNAs, lncRNAs, and circRNAs also contribute to the induction and maintenance of EMT-associated resistant phenotypes (59). In addition, some of these converge with the tumor stem cells (CSCs) activation pathways, where the induction of EMT in non-stem cells can promote radioresistance through the gain of stem-like characteristics.…”
Section: Radioresistancementioning
confidence: 99%